Venous malformation vessels are improperly specified and hyperproliferative. - Michael J Schonning; Seung Koh; Ravi W Sun; Gresham T Richter; Andrew K Edwards; Carrie J Shawber; June K Wu (PLoS ONE)
Venous malformations (VMs) are slow-flow malformations of the venous vasculature and are the most common type of vascular malformation with a prevalence of 1%. Germline and somatic mutations have been shown to contribute to VM pathogenesis, but how these mutations affect VM pathobiology is not well understood. The goal of this study was to characterize VM endothelial and mural cell expression by performing a comprehensive expression analysis of VM vasculature. VM specimens (n = 16) were stained for pan-endothelial, arterial, venous, and endothelial progenitor cell proteins; proliferation was assessed with KI67. Endothelial cells in the VM vessels were abnormally orientated and improperly specified, as seen by the misexpression of both arterial and endothelial cell progenitor proteins not observed in control vessels. Consistent with arterialization of the endothelial cells, VM vessels were often surrounded by multiple layers of disorganized mural cells. VM endothelium also had a significant increase in proliferative endothelial cells, which may contribute to the dilated channels seen in VMs. Together the expression analysis indicates that the VM endothelium is misspecified and hyperproliferative, suggesting that VMs are biologically active lesions, consistent with clinical observations of VM progression over time.